Indonesian Rheumatologist Association (IRA) Recommendations for Diagnosis and Management of Peripheral Spondyloarthritis 2021 - Sumartini Dewi; Arief Nurudhin; Ayu Paramaiswari; R.M. Suryo Anggoro Kusumo Wibowo; Yulyani Werdiningsih; Surya Darma; Lita Diah Rahmawati; Rudy Hidayat; Sumariyono (Indonesian Rheumatology Association, 2021)
Objective. Spondyloarthritis recommendations are made to provide guidance in diagnosis, treatment, and monitoring of peripheral spondyloarthritis cases.Method. Literature searches were conducted online. The drafting team determines the levels of evidence (LOE) and grades of recommendation (GOR). After conducting a discussion, each recommendation that has been agreed upon by the drafting team is then classified based on the levels of evidence and grades of recommendation. The final step in the preparation of these recommendations is to determine the level of agreement (LOA) on each recommendation carried out by a team of panelists who have been appointed by IRA.Result. Thirty five recommendations regarding peripheral spondyloarthritis were compiled. There are 6 strong recommendation or GOR A for psoriatic arthritis and 8 recommendations for enteropathic arthritis.Conclusion. These recommendations provide directions for clinicians to diagnose and to manage peripheral spondyloarthritis.